Sexual predators : how to recognize them on the Internet and on the street : how to keep your kids away - Dean, Stephen (Silver Lake Pub., 2006)
This book deals with the risks posed by sexual predators in a thorough, rational way. It explains how and why they act as they do-online and in the real world. It uses actual cases to show how sex crimes happen. And it gives readers practical advice for how to avoid becoming victims. The cases in the book are taken from the author's original reporting and research. He has spent more than a decade working with law-enforcement agencies in their investigation and prosecution of sex offenders. He knows the details-the mechanics, the patterns, the habits-that sex offenders use to locate and select victims.